2021
DOI: 10.3389/fchem.2021.741444
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hydroxytyrosol-Donepezil Hybrids as Potential Antioxidant and Neuroprotective Agents

Abstract: It is well-accepted that the endogenous antioxidant protection system progressively decays in elderly people, and that the oxidative stress contributes to different neurodegenerative disorders such as Alzheimer’s Diseases (AD). The lower incidence of AD in countries which feature the Mediterranean Diet was associated to the high consumption of extra virgin olive oil and its polyphenolic fraction, in particular hydroxytyrosol. The protective role of these bio-phenols against oxidative stress, suggested that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…However, there are some limits related to the ideal administration of this mixture: first of all, not all the components are hydrophobic, and could, therefore, easily cross the biological membranes. In order to address and solve this problem, one could imagine the formation of a single liquid form, hydrophobic, through appropriate chemical reactions [243][244][245][246] and administered as eye drops [247,248]. With this method of formulation two important limits could be avoided: the degrading action in the gastrointestinal system and the bioavailability of the compounds following digestion [249][250][251].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limits related to the ideal administration of this mixture: first of all, not all the components are hydrophobic, and could, therefore, easily cross the biological membranes. In order to address and solve this problem, one could imagine the formation of a single liquid form, hydrophobic, through appropriate chemical reactions [243][244][245][246] and administered as eye drops [247,248]. With this method of formulation two important limits could be avoided: the degrading action in the gastrointestinal system and the bioavailability of the compounds following digestion [249][250][251].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of exogenous antioxidants, taken through diet, are added to those generated by endogenous antioxidants, as described. The integration of exogenous antioxidants could take place with the administration of vitamins A, C and E and Coenzyme Q10 [ 304 , 305 , 306 ]. In this review, the protective roles of some exogenous antioxidants (vitamin A, vitamin C, Coenzyme Q10, lutein, quercetin, PUFAs and curcumin), against the main eye pathologies, in which oxidative damage is directly involved, have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several HTyr derivatives were tested for their neuroprotective action. A report showed that a nitro-HTyr was able to reduce ROS in an SH-SY5Y neuroblastoma cell line treated with H 2 O 2 (100 μM, 30 min–3 h) and also was able to chelate several metal cations [ 259 ]. In another report, a series of alkyl nitrohydroxytyrosyl ether derivatives were synthesized from free HTyr and tested for their antioxidant effect in comparison with nitro-HTyr and free HTyr, using different assays, such as oxygen radical scavenging capacity (ORAC).…”
Section: Neuroprotective Effects Exerted By Htyr In Vitro In Vivo And...mentioning
confidence: 99%